Carthamus tinctorius L. extract activates insulin‐like growth factor‐I receptor signaling to inhibit FAS‐death receptor pathway and suppress lipopolysaccharides‐induced H9c2 cardiomyoblast cell apoptosis. Issue 12 (4th September 2019) - Tung, Chun‐Liang; Ju, Da‐Tong; Velmurugan, Bharath Kumar; Ban, Bo; Dung, Tran D.; Hsieh, Dennis J.‐Y.; P. Viswanadha, Vijaya; Day, Cecilia H.; Lin, Yueh‐Min; Huang, Chih‐Yang
Abstract: Carthamus tinctorius L. (Compositae) is used in Chinese medicine to treat heart disease and inflammation. In our previous study, we found that C. tinctorius L. inhibited lipopolysaccharides (LPS)‐induced tumor necrosis factor‐alpha (TNF‐α) activation, JNK expression, and apoptosis in H9c2 cardiomyoblast cells. The present study was performed to investigate the protective effect of C. tinctorius extract (CTF) on LPS‐challenged H9c2 myocardioblast cell and to explore the possible underlying mechanism. Cell viability assay showed that LPS treatment decreased the cell viability of H9c2 cell, whereas CTF treatment reversed LPS cytotoxicity in a dose‐dependent manner, especially in the LPS + CTF 25 (μg/mL) group. LPS treatment‐induced apoptosis was determined by transferase‐mediated dUTP nick end labeling assay, and by Western blot. LPS‐induced apoptotic bodies were decreased following CTF treatment. Expression of TNF‐α, FAS‐L, FAS, FADD, caspase‐8, BID, and t‐BID was significantly increased in LPS‐treated H9c2 cells. In contrast, it was significantly suppressed by the administration of CTF extract. In addition, CTF treatment activates antiapoptotic proteins, Bcl‐2 and p‐Bad, and downregulates Bax, cytochrome‐c, caspase‐9, caspase‐3, and apoptosis‐inducing factor expression. Furthermore, CTF exerted cytoprotective effects by activating insulin‐like growth factor‐I (IGF‐I) signaling pathway leading to downregulation of the apoptotic proteins involved in FAS death receptor pathway. In addition, AG1024 and IGF‐I receptor (IGF‐IR) inhibitor and siRNA silencing reverses the effect of CTF implying that CTF functions through the IGF‐IR pathway to inhibit LPS‐induced H9c2 apoptosis. These results suggest that treatment with CTF extract prevented the LPS‐induced apoptotic response through IGF‐I pathway.